Treatment of Severe Cases of Coronavirus with Stone Cells (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The coronavirus disease (COVID-19) is global became a pandemic and asymptomatic carriers and light symptoms of the upper respiratory tract are severe and acute various clinical conditions up to respiratory syndrome causedThe article describes severe cases of coronavirus dedicated to stem cell treatment.